Vocabulary Instruction Strategies Employed by Preschool Teachers - Melike Yörüko; Nihat Bayat (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
This study aims to determine the extent to which preschool teachers utilize vocabulary instruction strategies. The participants of the research conducted in a survey model consisted of 240 preschool teachers working in central districts of Antalya, Turkey. In this research, the Vocabulary Instruction Strategies Scale, designed for preschool teachers in a five-point Likert scale, and the 'Personal Information Form' were used as data collection tools. In accordance with the research questions pertaining to the employed strategies, descriptive statistics calculations were conducted. Furthermore, Mann Whitney U, Kruskal Wallis H, One Way Anova, and Independent Group t-tests were applied for inquiries related to demographic variables. As a result of the applied statistical analyses, it has been determined that the participants consisting of preschool teachers employed word teaching strategies at a high level. The participants' levels of employing vocabulary instruction strategies did not show any significant differences based on their educational level, years of service, the age group they teach, and the type of school where they work. Recommendations are provided in line with the findings obtained from the research.